Impact ofthe Mahabharata, the Great Epic in Assamese Literature - Neog, Pronita (International Journal of Psychosocial Rehabilitation, 2020)
TheMahabharata, one of the greatest epics oftheworld, hasbeen exertingitsinfluenceonthe minds of Indianpeoplethrough centuries. Composed by VedaVyasaand inlaid withmorethan onelakhslokas (verses) the Mahabharatais amatchless and spaciousvolumeof not only India butalsoofthewhole world. History,tales,philosophy, ethics, diplomacy, sociology and so on are thereinthisgreatliterary workwhich eventuallyputitself inthe core of everyone’sheart. Like other parts of India, the Mahabharata extends its sway in the state of Assam, its people, society, culture and literature. The Mahabharata comprises all the human attributes - Dharma (virtuousness)-Artha (means)-Kama (desires)-Moksha (salvation) etc. in such a way without which we cannot analyse the Assamese literature in its complete sense.This research paper aims at how the Mahabharata has been influencing Assamese Literaturefrom ancient times till today.